Characterization of Brucella abortus lipopolysaccharide macrodomains as mega rafts - Lapaque, Nicolas (2005)
The lipopolysaccharides (LPS) of intracellular Proteobacteria such as Brucella, Chlamydia, Legionella and Rickettsia, have properties distinct from enterobacterial LPSs. These properties include deficient LPS induction of host cell activation, low endotoxicity and resistance to macrophage degradation. Together these constitute key virulence mechanisms for intracellular survival and replication. We previously demonstrated that B. abortus LPS captured by macrophages was recycled back to the plasma membrane where it was found associated with macrodomains. Furthermore, this LPS interferes with the MHC class II (MHC-II) presentation of peptides to specific T cell hybridomas. Here, we characterized the Brucella LPS macrodomains by microscopy and biochemistry approaches. We show for the first time that LPS macrodomains act as detergent resistant membranes (DRMs), segregating several lipid-raft components, LPS-binding proteins and MHC-II molecules. Brucella LPS macrodomains remain intact for several months in macrophages and are resistant to the disruptive effects of methyl β-cyclodextrin. Fluorescent anisotropy measurements show that B. abortus LPS is responsible for the formation of rigid surface membrane complexes. In addition, relocalization of MHC-II molecules is observed in these structures. The effects of B. abortus LPS on membrane properties could be responsible for pathogenic effects such as the inhibition of MHC-II-dependent antigen presentation. © 2005 The Authors; Journal compilation © 2005 Blackwell Publishing Ltd.